Pathogenic Bacteria Associated with Respiratory Disease in Poultry with Reference to Pasteurella multocida - Masdooq, A.A.; Salihu, A.E.; Muazu, A.; Habu, A.K.; Ngbede, J.; Haruna, G.; Sugun, M.Y. (International Journal of Poultry Science, 2008)
In this study, lung samples of chickens slaugtered at abattoir in Jos South, Nigeria were tested for the presence of Pasteurella multocida and other aerobic bacteria. The identity of P. multocida was proved by mouse pathogenicity test. A total of 3000 chickens were examined at post-mortem and 500 samples with pneumonia were collected. All lungs and heart blood from 15 different commercially reared chicken flocks showed respiratory disorders. Blood agar supplemented with 10% sheep blood was used for isolation of the agents.32 (6.5%) P. multocida were isolated and identified. In addition, mouse pathogenicity test was carried out on P. multocida suspected isolates. Twelve (75%) of Isolates were all positive. This study showed that P. multocida is not the most prevalent bacterial infection among chicken population in Jos south.